PARALLEL MATRIX-MULTIPLICATION ALGORITHM ON NETWORK OF WORKSTATIONS - Rusdi Md. Aminuddin; Rosni Abdullah; Suhaidi Hassan (Program Studi Statistika Unisba, 2004)
Matrix multiplication is one of the important operations in scientific and engineering application. However, it is also one ofthe operations that are time consuming. Continuous researches have been conducted to improve this operation. One of thealternatives is to have the operation performed in parallel. However, these types of algorithms often carried out onexpensive supercomputers or multiprocessing systems. With the advancement of personal computers and networking, theuse of network of computers has become an advantage to the computing community. Although programming in suchenvironment is relatively harder compared to that of in shared memory multiprocessing environment, its advantagesoutweigh its complexity. In this paper, we introduce the concept of Network of Computers (NOW) or Cluster computingand present its advantages. We discuss matrix-multiplication algorithm and highlight one of the parallel matrixmultiplicationalgorithms. We present the comparison in terms of speed between serial algorithm and the parallel algorithmwhen we run them on our cluster. We end our discussion by outlining our future works.